Integrating Deep Learning and Islamic Values in Science Education: Fostering Healthy Lifestyles Among Elementary School Students - Apriyani, Rini; Abidin, Yunus; Irianto, Dede Margo; Mulyati, Tita; Sutini, Ai (Jurnal al-Thullab, 2025)
This study aims to apply the Deep Learning approach in science subjects to foster students' healthy attitudes towards the gift of hearing through in-depth scientific understanding and the reinforcement of Islamic spiritual values. This study uses a field study method with a quantitative approach. The research subjects consisted of 120 fifth-grade students at SDN 050 Cibiru. Data were collected through observation, interviews, and tests of concept understanding and healthy lifestyle attitudes. Data analysis was conducted by comparing the pre-test and post-test results using descriptive statistical tests. The results showed that the application of Deep Learning in science education significantly improved students' conceptual understanding of the human auditory system. In addition, there was an increase in healthy lifestyle attitudes, such as awareness of maintaining ear hygiene and avoiding the habit of listening to loud sounds. Students also demonstrated an understanding of spiritual values related to gratitude and responsibility for the gift of hearing. The application of Deep Learning in science learning is effective in fostering healthy lifestyles based on Islamic values. The integration of technology, innovative learning strategies, and spiritual values can strengthen character education in elementary schools. This article makes an important contribution to the development of learning strategies that synergize science and faith in the elementary education environment.